Driving Performance While Wayfinding On-Road & in an Interactive Driving Simulator - Cochran, Lauren Marchman (East Carolina University, 2015)
Rationale: Driving is a fundamental instrumental activity of daily living (IADL) and occupational therapists need practical, effective tools to evaluate clients’ fitness to drive. To be proficient at driving, one needs competency on the operational (manipulating pedals, steering wheel), tactical (negotiating obstacles), and strategic (navigation) levels. Few studies explore the strategic level. It is beneficial to determine if the strategic level of driving can be evaluated without an expensive, lengthy on-road test. Purpose: This study compared on-road driving performance during wayfinding using paper directions compared to GPS. A second question compared performance between on-road driving and driving in an interactive driving simulator (IDS). Typical clinical assessments tools, specifically the Trail Making Test B, Assessment of Motor & Process Skills (AMPS), and Useful Field of View (UFOV ®) were also compared with driving outcomes. Design: Counterbalancing testing order of simulated driving and on-road driving of two unfamiliar routes yielded eight conditions. Participants: Participants were 24 volunteer drivers, ages 18-45 years. Methods: Each participant was assessed by the clinical assessments, navigated via printed directions on the driving simulator, and drove two routes on the road using either GPS guidance and printed directions. Driving performance was measured by the same evaluator using the same measuring tool. Analysis: Driving performance were compared with box plots, scatter plots, and a paired t-test with a 95% confidence interval. Clinical assessment scores were compared to driving scores on the simulator and on-road assessments using scatter plots. The two independent sample t-tests comparing groups defined by order was not statistically significant (p=.734; p=.805; p=.690). Results: The means of scores of participants wayfinding on road with GPS were significantly better than when using printed directions (p = .024; 95% CI = 1.58-20.7 points). Nineteen of 24 participants had better driving performance scores when using GPS. For participants using printed directions, the difference in mean scores for those driving in the simulator compared to on-road was not statistically significant (p=0.058). Outcomes of the clinical assessments did not have a strong relationship with any driving performance. Discussion: Performance using a GPS for wayfinding results in improved driving performance over printed directions. Overall, driving performance during wayfinding on an interactive driving simulator was similar to on-road driving performance, although there was individual variation. Limitations included a homogenous group of healthy participants and the driving simulator wayfinding was not a duplication of the on road route. This study suggests that wayfinding can be evaluated on an interactive driving simulator, offering opportunity for assessment of multiple client factors in a controlled environment and potentially reduce the number of individuals who need to proceed to an on road evaluation. It also supports that concept of using technology to support wayfinding for unfamiliar areas.
Keywords: Driving; Wayfinding; Driving simulator; Occupational Therapy; GPS; Navigation; Automobile Driving; Accidents, Traffic